Hubungan Kepatuhan Perawat Dalam Melaksanakan SPO Pemasangan Infus Dengan Kejadian Phlebitis Di Ruang Rawat Inap Teratai RSUP Fatmawati Jakarta: The Relationship between Nurse Compliance in Carrying out SOP for Infusion Installation and the Incident of Phlebitis in the Teratai Inpatient Room, Fatmawati Hospital, Jakarta - Suryadi, Suryadi (Dohara POAJ, 2024)
Introduction: Phlebitis is a vein infection that can occur due to chemical or mechanical irritation which manifests as marked redness, soreness and pain as well as swelling at the puncture site. The client appeared to indicate signs and symptoms of a new infection 72 hours after being admitted to the hospital. At the beginning of the client's admission there were no signs and symptoms of previous infection. If the problem of nosocomial infections is less than or equal to 1,5% the hospital can be said to have met the minimum service standards. The quality of hospital services can be influenced by the knowledge of nurses. The aim of this study was to determine the relationship between nurses' compliance in implementing SOP for infusion installation and the incidence of phlebitis in the Teratai inpatient ward, Fatmawati Hospital, Jakarta. Methods: This research uses Descriptive-Correlational with Cross-sectional. The population in this study were 135 executive nurses in class 2 and class 3 inpatient rooms at Fatmawati Hospital. The sampling technique used was accidental sampling. So, the sample in this study amounted to 88 respondents. The data collection technique used in this research is by using a questionnaire. This research uses the chi-square test. Results: Based on the research results it shows that respondents aged < 30 years have a higher percentage namely 54,4% or 48 respondents. Female gender is the majority with 74 respondents or a percentage of 84,1%. The respondent's education is a nurse with a total of 51 (58,0%) respondents. Based on the research results it shows that the majority of respondents, namely 76 (86,4%) comply with the SOP for infusion installation. Based on the research results, it shows that 57 respondents (64,8%). Based on the research results it shows that the results of statistical tests using chi-square obtained a p-value of 0,036 which is smaller than alpha (0,05). Discussion: Based on the research results it shows that respondents aged < 30 years have a higher percentage. Female gender is the majority with 74 respondents. Based on the research results it shows that the majority of respondents' education is nurses. Based on the research results it shows that the majority of respondents comply with the SOP for infusion installation. Based on the research results it showed that he did not experience phlebitis. There is a significant relationship between nurse compliance and the incidence of phlebitis.